2021
DOI: 10.1039/d0nr06401g
|View full text |Cite
|
Sign up to set email alerts
|

Size and ligand effects of gold nanoclusters in alteration of organellar state and translocation of transcription factors in human primary astrocytes

Abstract: Ultra-small gold nanoclusters are atomically precise structures that modulate organelles and redox-responsive transcription factors in human primary astrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Thus, the emergence of generalized principles governing the properties of clusters is deemed essential. Clearly, quantum chemistry methods elucidating the geometry of the clusters and configuring their optical properties in terms of molecular transitions should be conducted in further depth for the assembly of clusters, and innovative approaches such as the hybrid QM/MM (quantum mechanics/molecular mechanics) approach might address their structure–properties relationships [ 117 , 118 , 119 , 120 , 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the emergence of generalized principles governing the properties of clusters is deemed essential. Clearly, quantum chemistry methods elucidating the geometry of the clusters and configuring their optical properties in terms of molecular transitions should be conducted in further depth for the assembly of clusters, and innovative approaches such as the hybrid QM/MM (quantum mechanics/molecular mechanics) approach might address their structure–properties relationships [ 117 , 118 , 119 , 120 , 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study on human primary astrocytes demonstrated that AuNCs were not inert within the cells. Even though no significant cell loss has been observed for AuNC concentrations below 10 µM, alterations were detected in the organellar and redoxresponsive transcription factor homeostasis [133]. These effects may also depend on the nature of the ligands.…”
Section: Biological Properties Of Auncs 231 Cellular Uptake-internalization Mechanisms and Cytotoxicitymentioning
confidence: 91%
“…Solvent accessibility has been found to play a critical role in the luminescence properties of ligated gold NCs. It is strongly dependent on the nature of ligands and the size of MNCs [ 62 , 63 ]. Aurophilic interactions between interlocked Au(I)-thiolate ring structures for Au 10 SG 10 catenane NCs [ 64 , 65 ] cause the enhancement of the luminescence for Au(I) oligomers.…”
Section: On the Structure–optical Properties Relationship Of Metal Na...mentioning
confidence: 99%